IMPLIKASI PROGRAM RUMAH GEMILANG INDONESIA LAZ AL-AZHAR PERWAKILAN JAWA TIMUR TERHADAP KESEJAHTERAAN ALUMNI - Nur Sayuta, Rizqi Bhakti; Ajeng Kartika Galuh (Islamic Economics and finance in Focus, 2024)
This research aims to determine the implications of Rumah Gemilang Indonesia, which is an empowerment program from LAZ Al-Azhar representative of East Java of alumni welfare. In this research, quantitative methods are used with a multiple linier regression approach which uses classical assumpsion tests in the form of normality tests, heteroscedasticity tests, and muticollinearity tests. This research examined 50 alumni data from Rumah Gemilang Indonesia. In this research, it shows that the education variable and the income variable have a simultaneous effect based on the F tests, and have a partial effect based on the T tests, and show that the percentage of influence of the education variable and the walfare variable is 80,6% (R-Square) while it is 19,6% the other is influenced by other variables not examined in this study. In general, this research shows that Rumah Gemilang Indonesia is able to make alumni prosperous so that LAZ Al-Azhar as a zakat amil institution that owns the program plays a maximum role. This research complements previous research by using quantitative methods so that the implocations of LAZ Al-Azhar can be seen and taken into account as a matter of more precise with numbers and calculations using the SPSS 25 data processing application